Nanosecond modulation of thermal emission - Wasserman, Daniel (Light Sci Appl, 2019)
Femtosecond laser pulses are used to modulate the thermal emission from semiconductor materials at the nanosecond timescale. A visible-frequency laser photoexcites energetic free carriers in intrinsic Si and GaAs wafers. As these free carriers return to equilibrium, they not only emit thermal radiation on a picosecond time scale but also modulate the semiconductor thermal emission on a nanosecond to microsecond time scale, offering a novel route towards ultrafast infrared optical pulses.